KELAYAKAN TEKNIS DAN FINANSIAL PEMBUATAN BIOBRIKET DARI LIMBAH PADAT KELAPA SAWIT DENGAN METODE PENGARANGAN - Budiyanto Budiyanto; Pandu Imam Sudibyo Adib; Yohannes Adimar Marbun (Jurnal Agroindustri, 2011)
This research was conducted at the Laboratory of Agricultural Technology, University of Bengkulu and Laboratory of PT Sucofindo Bengkulu, from May until August 2009. This study compared three types of biobriquettes such as the biobriquettes made of shell charcoal, coal-mixed TTKS charcoal biobriquettes, and coal-mixed TKKS charcoal with carbonized-coal briquettes. The results showed that, technically, biobriquettes has cylindrical dimension with a diameter of 4.5 cm, height 7 cm, lower hole diameter 1.5 cm, and upper hole diameter  1.2 cm. Biobriquette made of TKKS charcoal is very feasible to use as used as a fuel in compare to carbonized-coal briquettes, since TKKS charcoal biobriquette contains 7, 3 % water and the average calorific value of 6141 kcal / kg. Financially, the manufacturing on these three types of palm oil waste briquettes is very feasible because it has R/C value > 1. However, if these three types compared, coal-mixed TTKS charcoal biobriquettes is preferable because it has R/C value 1,78 with break-even-point (BEP) 24.468 kg/ year, which is better than biobriquettes made of TKKS charcoal and shell charcoal.